Perfil epidemiológico de pessoas com acidente vascular cerebral e suas barreiras arquitetônicas domiciliares - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Contextualization: Cerebral Vascular Accident is the main cause of death and disability in Brazil and generates high costs to the public coffers. Despite the decline in the mortality rate in recent year, attention to actions to combat the disease is fundamental to the development of public health. Objetive: To investigate the epidemiological profile and home architectural barriers of people with a diagnosis of stroke, belonging to the Family Health Strategy 2. Methodology: A quantitative, exploratory and field research was carried out, applying an identification questionnaire, as well as two instruments for evaluating housing, one of them being self-perception. Results: Sample had 17 people, most of them had some neurological deficit, which in a way affected their daily activities. A close relationship between modifiable and non-modifiable factors was found. Their homes showed themselves with structural and unadapted deficiencies, and through self-report people did not consider them inadequate. Conclusion: Ischemic stroke was the most frequent, its development seemed to be associated mainly with age and chronic diseases such as hypertension and DM. These results showed the need for a well-structured basic care, able to prevent the main risk factors. The residences presented a series of structural problems, but the resident analyzed seems to be well adapted.
Epidemiological profile of people with stroke and their home architectural barriers
Keywords: Stroke; Epidemiology; Basic attention; Promotion and prevention; Architectural barriers; Acidente Vascular Cerebral; Epidemiologia; Atenção básica; Promoção e prevenção; Barreiras arquitetônicas; AVC; Saúde pública; CNPQ::CIENCIAS DA SAUDE